2011
DOI: 10.1021/ja202732q
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of a Partial Ru–O Bond during the Metal–Ligand Bifunctional Addition in Noyori-Type Enantioselective Ketone Hydrogenation

Abstract: The transition state for the metal-ligand bifunctional addition step in Noyori's enantioselective ketone hydrogenation was investigated using intramolecular trapping experiments. The bifunctional addition between the Ru dihydride trans-[Ru((R)-BINAP)(H)(2)((R,R)-dpen)] and the hydroxy ketone 4-HOCH(2)C(6)H(4)(CO)CH(3) at -80 °C exclusively formed the corresponding secondary ruthenium alkoxide trans-[Ru((R)-BINAP)(H)(4-HOCH(2)C(6)H(4)CH(CH(3))O)((R,R)-dpen)]. Combined with the results of control experiments, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 68 publications
3
42
0
1
Order By: Relevance
“…This is the equivalent question, discussed in the literature, as to whether such dihydride complexes react with acetophenone to give directly the alcohol and the amido complex 1 via H + /Htransfer to the ketone in the transition state (path 2 to a polarized TS, then path 3 to 1, and then path 4 to the alkoxide complex 3 of Scheme 2) 1; 2; 4; 5; 7; 30 or to give an alkoxide complex 3 via an initial hydride transfer (path 2 to an ion pair TS that includes a hydrogenbonded alkoxide, then path 5 to 3 in Scheme 2). 19; [31][32][33][34][35][36] Arguments have been made for each pathway depending on the solvent and other conditions. An observation in the current work is that the alkoxide forms quickly from the amido complex and alcohol and is more prevalent at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…This is the equivalent question, discussed in the literature, as to whether such dihydride complexes react with acetophenone to give directly the alcohol and the amido complex 1 via H + /Htransfer to the ketone in the transition state (path 2 to a polarized TS, then path 3 to 1, and then path 4 to the alkoxide complex 3 of Scheme 2) 1; 2; 4; 5; 7; 30 or to give an alkoxide complex 3 via an initial hydride transfer (path 2 to an ion pair TS that includes a hydrogenbonded alkoxide, then path 5 to 3 in Scheme 2). 19; [31][32][33][34][35][36] Arguments have been made for each pathway depending on the solvent and other conditions. An observation in the current work is that the alkoxide forms quickly from the amido complex and alcohol and is more prevalent at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Bergens et al. later proposed that a partial RuO bond or a strong H‐bond between NH and alkoxide could be present in the transition state based on the observed formation of alkoxide intermediates at low temperatures 12…”
Section: Metal–ligand Cooperation Through Ml Bondsmentioning
confidence: 99%
“…19 Conversely, Bergens reported that [Ru(H) 2 (binap)(dpen)] reacts with acetophenone leading to [RuH(OR)(binap)(dpen)] at low temperature 20. The formation of the Ru‐amide and 1‐phenylethanol occurs at a subsequent step and an alternative pathway involving a transition state with a partial RuO linkage has been proposed 21. Evidence of the formation of alkoxides [RuH(OR)(PP)(1,2‐diamine)] and alcohol complexes [RuH(HOR)(PP)(1,2‐diamine)] + , which are involved in the heterolytic cleavage of H 2 has been provided by the groups of Morris,18 Noyori,22 and Bergens 23.…”
Section: Introductionmentioning
confidence: 99%